Spirit of the Mind : Divine Disclosure, Nafs and the Transcendental Self in Islamic Thought - Khan, Sanaullah (Brill Research Perspectives in Humanities and Social Sciences., 2025)
In Spirit of the Mind , Khan delves into Islamic perspectives on the soul and its implications for spirituality and self-cultivation. Despite varying views on the soul's composition, a shared belief has persisted among theologians, scholars, preachers and reformists that it bears traces of the divine. Thus, drawing closer to God and gaining knowledge of nature involve returning to the soul's natural state of perfection. Central to Islamic thought is the struggle between the soul and the nafs (lower self), embodying carnal desires. In this context, achieving closeness to God requires purifying the soul to control the nafs . Khan traces a genealogy of the Islamic notion of the soul by exploring disturbances of the soul through Greek humoral theory, notions of spiritual weakness as deviation from perfection, the heart representing the seat of the soul, and the soul's aspiration for the divine light ( nur ) for its purification. Khan reflects on Islamic notions of the self through the tradition of the Perfect Man which emphasizes spiritual ascent and divine proximity. Overall, the monograph offers a nuanced exploration of the soul's significance in Islamic thought, highlighting the what thinkers have considered as the path to divine proximity and enlightenment.